1969
DOI: 10.1017/s0007485300056005
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural studies of Glossina morsitans Westw. using tantalum-182

Abstract: Investigations, using tantalum-182, into the behaviour of Glossina morsitans Westw. in large field cages are described. Individual straight-line displacements occurred on average about every three hours and were generally small and erratic in direction. The perimeters of the cages tended to ‘ trap ’ an enclosed population, but flies appeared to move to the walls more quickly when they were shaded by an outer covering of hessian. Horizontal distribution and movements of flies did not appear to be associated dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1969
1969
1986
1986

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“…Virgin and pregnant females of G. m. morsitans were extremely inactive, displaying between three and 25 movements in four and a half hours, which compares with the findings of Dean et al (1969) who recorded a single displacement, on average, every three hours. Bursell (1957) observed individuals remaining stationary for 10 h or more, and Brady (1972a) recorded only 12 min of activity per day.…”
Section: General Activitysupporting
confidence: 63%
“…Virgin and pregnant females of G. m. morsitans were extremely inactive, displaying between three and 25 movements in four and a half hours, which compares with the findings of Dean et al (1969) who recorded a single displacement, on average, every three hours. Bursell (1957) observed individuals remaining stationary for 10 h or more, and Brady (1972a) recorded only 12 min of activity per day.…”
Section: General Activitysupporting
confidence: 63%
“…This pattern of activity and inactivity has been compared by Brady (1970) to the known course of proline consumption and recovery during periods of flight and rest (Bursell, 1963). Bursts of activity in the laboratory can be presumed to represent the short flights of wild flies searching their natural environment (Dean, Williamson & Phelps, 1969;Bursell, in Mulligan & Potts, 1970). Those ' searching' flies which eventually find an attractive food source have been shown to contain less proline and more alanine and glutamate, suggesting they had been more active, than other flies caught from the ' swarm' following a fly round party (Bursell & Slack, 1969).…”
Section: Activity and Behaviourmentioning
confidence: 99%
“…The work of Vale (1971) on natural and artificial refuge resting sites has already been discussed (p. 365). Dean, Williamson & Phelps (1969), also in Rhodesia, fixed small pieces of tantalum-182 wire to the thorax of G. m. morsitans and detected resting flies with a radiation monitor in large cages. Results were unsatisfactory in that most flies rested on the walls of the cages ; it was concluded that most flies rested 6-10 ft above the ground, although some occurred at ground level and others at 30 ft.…”
Section: Breeding Sitesmentioning
confidence: 99%
“…This has been shown to be the period of peak diurnal feeding activity of G. m. suhmorsitans (Davies, 1967) and the closely related G. m. morsitans (Pilson and Pilson, 1967;Dean et al, 1969). This has been shown to be the period of peak diurnal feeding activity of G. m. suhmorsitans (Davies, 1967) and the closely related G. m. morsitans (Pilson and Pilson, 1967;Dean et al, 1969).…”
Section: Discussionmentioning
confidence: 98%